Beyond the Distinction Between Biomedical and Social Dimensions of HIV Prevention Through the Lens of a Social Public Health - Kippax, Susan (American Public Health Association, 2012)
Developing effective HIV prevention requires that we move beyond the historical but problematic distinction between biomedical and social dimensions of HIV. The current claim that prevention has failed has led to a strong interest in the role of treatment as HIV prevention; however, the turn to “biomedical prevention,” “test and treat,” and “combination prevention” instances pervasive confusions about prevention. These confusions arise from a failure to realize that all HIV prevention interventions must engage with the everyday lives of people and be integrated into their social relations and social practices. We challenge the claim that prevention has failed (illustrating this with discussion of prevention in Australia, Uganda, and Zimbabwe). We explain the enduring appeal of misguided approaches to prevention by examining how 1996 can be seen as a pivotal moment in the history of the global response to HIV, a moment marked by the rise and fall of distinct biomedical and social narratives of HIV.